Peran Minat dan Interaksi Siswa dengan Guru Dalam Meningkatkan Hasil Belajar Matematika - Chatarina Febriyanti; Seruni Seruni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
The objective of this research is to find and analyze empirically the influence of student and teacher interaction and interest in learning toward math learning outcomes. The population in this study is the affordable class VII student DPN 86 South Jakarta. 70 samples are obtained through random sampling method. The research design used through correlation with three variables consisting of two independent variables, namely the interaction of students and teachers and the interest in learning as well as the dependent variable, namely the learning outcomes matemtika. Data was collected through questionnaire techniques (variable student and teacher interaction and interest in learning) and test techniques (variable learning outcomes). The collected data were then analyzed using correlation and multiple regression techniques. Before the data were analyzed, first performed descriptive statistical analysis and test data requirements (normality test, linearity, and multicollinearity test). The results showed that: there is a significant relationship between student and teacher interaction and interest in learning the mathematics learning outcomes, with a correlation coefficient of 0.877 and a coefficient of determination 0.768 or 76.8% of students and teacher interaction and interest in learning jointly affect learning outcomes mathematics. The resulting regression equation Y = - 41.565 + 0.659 X1 + 0.371 X2. This may imply that the better interaction of students and teachers the better the learning outcomes and the higher the higher the interest in learning math learning outcomes.